Experience of work St. George the Martyr Hospital in the influenza epidemic H1N1 in 2009 - Yu. M. Gomon; V. V. Kozlov; A. A. Domashenko; O. A. Grinenko (Журнал инфектологии)
The article presents the experience of conversion multi-disciplinary somatic hospitals in the infectious hospital. In November-December 2009, the hospital carried out 602 care to patients with acute respiratory infections and influenza, 61 had confirmed influenza caused by virus H1N1, of which 43 patients were hospitalized in serious and critical condition and needed resuscitative benefits. Arising from the conversion to ensure that the complexity of medical-diagnostic process and the observance of sanitary-epidemiological rules for patients suffering from the flu, demanded the mobilization of all forces and resources of the hospital, additional equipment, purchases of non-core drugs. We obtained the experience can be a great help in such situations with re-profiling of general somatic hospitals in infection.